Has dopamine a physiological role in the control of sexual behavior? A critical review of the evidence - Paredes, Raúl G; Agmo, Anders (Progress in neurobiology, 2004)
The role of dopaminergic systems in the control of sexual behavior has been a subject of study for at least 40 years. Not surprisingly, reviews of the area have been published at variable intervals. However, the earlier reviews have been summaries of published research rather than a critical analysis of it. They have focused upon the conclusions presented in the original research papers rather than on evaluating the reliability and functional significance of the data reported to support these conclusions. During the last few years, important new knowledge concerning dopaminergic systems and their behavioral functions as well as the possible role of these systems in sexual behavior has been obtained. For the first time, it is now possible to integrate the data obtained in studies of sexual behavior into the wider context of general dopaminergic functions. To make this possible, we first present an analysis of the nature and organization of sexual behavior followed by a summary of current knowledge about the brain structures of crucial importance for this behavior. We then proceed with a description of the dopaminergic systems within or projecting to these structures. Whenever possible, we also try to include data on the electrophysiological actions of dopamine. Thereafter, we proceed with analyses of pharmacological data and release studies, both in males and in females. Consistently throughout this discussion, we make an effort to distinguish pharmacological effects on sexual behavior from a possible physiological role of dopamine. By pharmacological effects, we mean here drug-induced alterations in behavior that are not the result of the normal actions of synaptically released dopamine in the untreated animal. The conclusion of this endeavor is that pharmacological effects of dopaminergic drugs are variable in both males and females, independently of whether the drugs are administered systemically or intracerebrally. We conclude that the pharmacological data basically reinforce the notion that dopamine is important for motor functions and general arousal. These actions could, in fact, explain most of the effects seen on sexual behavior. Studies of dopamine release, in both males and females, have focused on the nucleus accumbens, a structure with at most a marginal importance for sexual behavior. Since accumbens dopamine release is associated with all kinds of events, aversive as well as appetitive, it can have no specific effect on sexual behavior but promotes arousal and activation of non-specific motor patterns. Preoptic and paraventricular nucleus release of dopamine may have some relationship to mechanisms of ejaculation or to the neuroendocrine consequences of sexual activity or they can be related to other autonomic processes associated with copulation. There is no compelling indication in existing experimental data that dopamine is of any particular importance for sexual motivation. There is experimental evidence showing that it is of no importance for sexual reward.